Development of a feasible and responsive ultrasound inflammation score for rheumatoid arthritis through a data-driven approach. Issue 2 (16th December 2016) - Aga, Anna-Birgitte; Berner Hammer, Hilde; Christoffer Olsen, Inge; Uhlig, Till; Kvien, Tore K; van der Heijde, Désirée; Fremstad, Hallvard; Madland, Tor Magne; Lexberg, Åse Stavland; Haukeland, Hilde; Rødevand, Erik; Høili, Christian; et al.
Abstract : Objective: To develop and validate a responsive and feasible ultrasound inflammation score for rheumatoid arthritis (RA). Methods: We used data from cohorts of early RA (development) and established RA starting/switching biologic therapy (validation). 4 tendons and 36 joints were examined by a grey scale (GSUS) and power Doppler semiquantitative ultrasound (PDUS) scoring system (full score). Ultrasound score components were selected based on factor analyses of 3-month change in the development cohort. Responsiveness was assessed by standardised response means (SRMs). We assessed the proportion of information retained from the full score by linear regression. Results: 118 patients with early and 212 patients with established RA were included. The final ultrasound score included 8 joints (metacarpophalangeal 1–2–3, proximal interphalangeal 2–3, radiocarpal, metatarsophalangeal 2–3) and 1 tendon (extensor carpi ulnaris) examined bilaterally. The 6-month SRMs for the final score were −1.24 (95% CI −1.47 to −1.02) for GSUS, and −1.09 (−1.25 to −0.92) for PDUS in early RA, with 87% of total information retained for GSUS and 90% for PDUS. The new score performed somewhat better than formerly proposed scores in the validation cohort. Conclusions: The Ultrasound in Rheumatoid Arthritis 9 joint/tendon score (USRA9) inflammation score showed good responsiveness, retained most of the information from the original full score and overall performed better than previous scores in a validation cohort. Trial registration numbers: NCT01205854, ACTRN12610000284066; Post-results.